Dispensasi Hukum Perkawinan di Bawah Umur Perspektif Hukum Islam dan Hukum Nasional - Afandi, Ahmad; Billah, Muhammad Erfan Muktasim; Siddiq, Mahfudz (LPPM Institut Pendidikan Nusantara Global, 2024)
Article 7 Paragraph 1 of Law Number 16 of 2019 stipulates that the minimum age for marriage is 19 years. However, marriages below this age are still possible through a dispensation regulated by law. This study analyzes the perspectives of Islamic law and national law regarding marriage dispensations following the amendment to the minimum marriage age in Law Number 16 of 2019. Additionally, this study evaluates the impact of the amendment. The method used is normative legal research, focusing on the study of legal rules and principles. Based on the research findings, Islamic law tends to be more flexible in granting dispensations, while national law has become stricter following the amendment. The impact of the minimum marriage age change is reflected in the decline in the number of dispensation requests, indicating increased public awareness of the importance of education and delaying marriage. This change is expected to support the development of future generations' quality.